COMPARISON OF SANDWICH COMPOSITE WING STRUCTURE WITH BALSA WOOD (CASE STUDY OF UAV AIRCRAFT FIXED WING VTOL VX-2) - Santoso, Djarot Wahju; Hariyanto, Kris (Vortex, 2022)
UAV aircraft with a fixed wing configuration with multi-rotor are aircraft capable of vertical take-off and landing (VTOL). In designing the wing structure of aircraft, the weight factor and the strength of the wing structure are factors that need to be considered. The use of sandwich composite materials on UAV wings is expected to be able to meet the requirements of UAV aircraft, namely having a light weight, having high rigidity and strength. In this study, a comparative analysis the strength of the sandwich composite wing structure with the balsa wood wing of the UAV VTOL VX-2 aircraft was carried out. The steps taken are to model the composite wing structure of sandwiches and balsa wood using CATIA. Performing the process of structural analysis using ANSYS software. Both half-span models are subjected to lift and vertical take-off loads. From the analysis results, the sandwich composite wing (glass fiber skin with styrofoam core) is stronger than the balsa wood wing structure under vertical take off loads. While the VTOL rods, upper and lower spars of the balsa wood wing model are stronger than the sandwich structure under lift loads, but overall the sandwich wing structure is stronger than the balsa wood wing